2014
DOI: 10.1074/jbc.m114.606517
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Blockade of Sialylation in Mice with a Global Inhibitor of Sialyltransferases

Abstract: Background:In vivo pharmacological inhibition of sialyltransferases has, to date, not been possible. Results: 3F-NeuAc acts as a global sialyltransferase inhibitor in mice and causes kidney and liver dysfunction. Conclusion: Sialoside expression can be modulated in vivo with a sialyltransferase inhibitor. Significance: Pharmacological blockade of sialoside expression will be an important tool for future exploration of sialic acid in health and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 46 publications
6
86
0
1
Order By: Relevance
“…For example, the heavily sialylated protein podocalyxin on glomerular podocyte foot processes (474)(475)(476)(477)(478) and heparan sulfate glycosaminoglycans within the glomerular basement membrane (479)(480)(481)(482)(483)(484) seem to play important roles in maintaining the integrity of blood plasma filtration by the kidney. Pathological or experimental damage to such glycans causes large molecules like albumin to escape into the urine, and is associated with glomerular diseases (478,(485)(486)(487)(488)(489)(490)(491).…”
Section: Diffusion Barriersmentioning
confidence: 99%
“…For example, the heavily sialylated protein podocalyxin on glomerular podocyte foot processes (474)(475)(476)(477)(478) and heparan sulfate glycosaminoglycans within the glomerular basement membrane (479)(480)(481)(482)(483)(484) seem to play important roles in maintaining the integrity of blood plasma filtration by the kidney. Pathological or experimental damage to such glycans causes large molecules like albumin to escape into the urine, and is associated with glomerular diseases (478,(485)(486)(487)(488)(489)(490)(491).…”
Section: Diffusion Barriersmentioning
confidence: 99%
“…Paulson and co-workers reported peracetylated analogs of sialic acid bearing a fluorine atom proximal to the endocyclic oxygen (P-3F ax -Neu5Ac, 1, Fig. 3) as a cell-permeable specific inhibitor of the sialyltransferases [21,22]. This is an elegant approach by taking advantage of the relaxed substrate specificity of enzymes in the sialic acid salvage pathways and its ability to accommodate unnatural analogs of sialic acid.…”
Section: Sialic Acid Analogsmentioning
confidence: 99%
“…Recently a study has reported the pharmacologic potential of cell permeable inhibitors of both FucTs and sialyltransferases. These are fluorinated analogs of fucose and sialic acids and have been shown to inhibit fucosylation and sialylation in vitro [168, 169] .…”
Section: Glycans As Therapeutic Targetsmentioning
confidence: 99%